1994
DOI: 10.1016/0550-3213(94)90213-5
|View full text |Cite
|
Sign up to set email alerts
|

Charm and bottom production: theoretical results versus experimental data

Abstract: We present recent theoretical results in heavy-quark production, and we compare them with available experimental data. In particular, we consider the total cross sections, the x F and p 2 T single-inclusive distributions, and results on heavy-quark pair correlations in both hadroproduction and photoproduction of charm and bottom hadrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
155
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(166 citation statements)
references
References 70 publications
11
155
0
Order By: Relevance
“…Neither leading-order nor next-to-leading-order perturbative QCD calculations of charm quark production can account for the observed asymmetries [10,11]. The phenomenon is due either to unexpected contributions to charm quark production or to features of the hadronization process.…”
Section: Introductionmentioning
confidence: 95%
“…Neither leading-order nor next-to-leading-order perturbative QCD calculations of charm quark production can account for the observed asymmetries [10,11]. The phenomenon is due either to unexpected contributions to charm quark production or to features of the hadronization process.…”
Section: Introductionmentioning
confidence: 95%
“…The total cross section is strongly dependent on QCD parameters such as the heavyquark mass, parton distributions, and factorization and renormalization scales. It is not our aim here to present theoretical limits and errors -this has been done elsewhere [13]. However, Fig.…”
Section: Properties Of the Perturbative Productionmentioning
confidence: 99%
“…Depending on the choice of cut-off parameters, the latter may give negative differential cross sections in some regions of phase space. The divergences disappear in sufficiently inclusive distributions, so much phenomenological insight can be gained [13]. However, with our currently available set of calculational tools, the NLO approach is not so well suited for the exclusive Monte Carlo studies we have in mind here, where hadronization is to be added on to the partonic picture.…”
Section: Perturbative Aspects 211 Production Mechanismsmentioning
confidence: 99%
“…Other data also suggest k T values larger than those expected from NLO PQCD calculations. Recent comparisons of p T spectra from charm-particle hadroproduction to NLO PQCD results provide evidence that supplemental k T may be required to properly describe the data [6]. Likewise, it has been suggested that the observed pattern of discrepancies between data from various direct-photon experiments and results from NLO PQCD calculations could be related to k T effects [7].…”
mentioning
confidence: 99%